Leveraging Geospatial Technology for Financial Inclusion : Financial Inclusion Support Framework - Ul Haq, Imtiaz; Gradstein, Helen Luskin (World Bank, Washington, DC, 2020)
Geospatial technology can be used to map financial access points and assess the distribution of financial services across space, allowing authorities to identify gaps in existing coverage clearly and with much higher precision than is otherwise possible. It can also help to prioritize gaps with respect to various policy objectives as well as design appropriate policy interventions at a subnational level. This note provides financial sector authorities and other stakeholders practical guidance for leveraging geospatial tools to inform financial inclusion policymaking. It draws from the work conducted in Ethiopia, Mozambique and Pakistan under the Financial Inclusion Support Framework (FISF) program.